The impact of mutations on TP53 protein and MicroRNA expression in HNSCC: Novel insights for diagnostic and therapeutic strategies - Ashraf Attia Mahmoud; Mohd Firdaus Raih; Edison Eukun Sage; Qurashi M. Ali; Omnia H. Suliman; Sabah A. E. Ibrahim; Osama Mohamed; Samar Abdelrazeg; Sofia B. Mohamed (PLoS ONE, 2025)
The tumor suppressor protein p53 (TP53) is frequently mutated in various types of human malignancies, including HNSCC, which affects tumor growth, prognosis, and treatment. Gaining insight into the impact of TP53 mutations in HNSCC is crucial for developing new diagnostic and therapeutic methods. In this study, we aimed to investigate the influence of mutations on the structure and functions of the TP53 protein and miRNA expression using computational analysis. The genomic data of patients with HNSCC were obtained from TCGA, and the impact of mutations on the TP53 gene was investigated using different bioinformatics tools. Results: The findings showed that the TP53 mutations increased TP53 expression levels in HNSCC and were associated with a poor prognosis. Furthermore, hsa-mir-133b expression was reduced in TP53-mutated samples, significantly affecting patient survival in HNSCC. Six mutations, including R273C, G105C, G266E, Q136H/P, and R280G, were identified as deleterious, carcinogenic, driver, highly conserved, and exposed. These mutations were located in the P53 domain, and PTM analysis revealed that R280G and R273C are at a methylation site, and R273C, Q136H/P, and R280G are located in the protein pocket. The docking research indicated that these mutations decreased the binding affinity for DNA, with R273C, R280G, G266E, and G105C displaying the most significant differences. The molecular dynamics analysis indicates that R280G, Q136H, and G105C mutations confer a gain of function by stabilizing the TP53-substrate complex. Conclusions: Based on the research findings, the mutations on TP53 were found to have an impact on protein and miRNA expression, development, survival, and progression of HNSCC patients, and has-mir-133b could be a promising novel biomarker for monitoring the progression of HNSCC. It was discovered that G105C and Q136H/P, as novel mutations, affect the function and structure of proteins causing HNSCC, which indicates that they could be interesting subjects for further investigation, diagnostics, and therapeutic strategies. Furthermore, the precise positioning of R280G and R273C within the methylation site and Q136H/P in the binding site has been documented for the first time. Moreover, the G105C, Q136H, and R280G mutations that stabilized TP53 structure and altered its interaction dynamics with substrates may serve as novel potential diagnostic biomarkers in cancer, guiding patient stratification and personalized treatment strategies. The molecular dynamics analysis provides insights into how specific TP53 mutations impact protein structure, stability, and function upon substrate binding, highlighting their role in cancer biology and potential implications for therapeutic interventions. This paper provides a novel understanding of the mechanisms by which these mutations contribute to the development of cancer.